Securitizing Islam : identity and the search for security - Croft, Stuart (Cambridge; New York : Cambridge University Press, 2012)
"Securitizing Islam examines the impact of 9/11 on the lives and perceptions of individuals, focusing on the ways in which identities in Britain have been affected in relation to Islam. 'Securitization' describes the processes by which a particular group or issue comes to be seen as a threat, and thus subject to the perceptions and actions which go with national security. Croft applies this idea to the way in which the attitudes of individuals to their security and to Islam and Muslims have been transformed, affecting the everyday lives of both Muslims and non-Muslims. He argues that Muslims have come to be seen as the 'Other', outside the contemporary conception of Britishness. Reworking securitisation theory and drawing in the sociology of ontological security studies, Securitizing Islam produces a theoretically innovative framework for understanding a contemporary phenomenon that affects the everyday lives of millions"--
Machine generated contents note: Introduction; 1. Ontological security and Britishness; 2. A post-Copenhagen securitization theory; 3. 'Two World Wars and one World Cup': constructing contemporary Britishness; 4. 'New Britishness' and the 'new terrorism'; 5. The construction of ontological insecurity; Conclusion.
Includes bibliographical references (pages 262-270) and index.
Keywords: Terrorism -- Prevention -- Government policy -- Great Britain; Terrorism -- Social aspects -- Great Britain; Terrorism -- Religious aspects -- Islam; Islam -- Great Britain; Muslims -- Great Britain; Islamic fundamentalism -- Great Britain; Internal security -- Great Britain; National security -- Social aspects -- Great Britain; September 11 Terrorist Attacks, 2001 -- Influence; POLITICAL SCIENCE / International Relations / General; Great Britain -- Public opinion